PENGARUH PDRB PER KAPITA, KEPADATAN PENDUDUK, TINGKAT PENDIDIKAN DAN BELANJA LINGKUNGAN HIDUP TERHADAP TIMBULAN SAMPAH DI PULAU JAWA TAHUN 2010-2019 - Lavany, Mitha Qurrota Ayyun (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Provinces on the island of Java contribute greatly to national economic growth. However, this is not enough to be an indicator of development. Economic growth not only generates positive externalities but also generates waste. Other socio-economic characteristics also play a role in variations in the amount of waste generation, so it is important to study it for sustainable development planning. This study aims to analyze the effect of economic growth proxied by per-capita GRDP on waste generation on the island of Java in 2010-2019 and test its suitability with the Environmental Kuznet Curve (EKC) hypothesis. This study also analyzes the influence of other variables such as population density, education level and the government's role in spending on environmental management in Java. The analysis technique used is panel data regression using data from 6 provinces in Java during the 2010-2019 period. By using two model specifications, the results of the study show that the effect of economic growth on waste generation has not fully formed the EKC curve, but rather has a positive slope. The population density variable shows a positive and significant effect on waste generation. While the level of education and environmental spending have a negative effect on waste generation, it is not significant for BLH. The results of this study can support policy implications in encouraging new strategies to reduce waste generation and integrate environmental management.